1999
DOI: 10.1046/j.1439-0272.1999.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Normal sperm morphology and chromatin packaging: comparison between aniline blue and chromomycin A3 staining

Abstract: The successful implementation of ICSI has provided a unique means of allowing couples suffering from severe male infertility to achieve their reproductive goals. However, despite the great therapeutic advantages of the technique, ICSI often provides solutions to clinicians in the absence of an aetiological or pathophysiological diagnosis. The development of a sequential diagnostic schedule for patients consulting for fertility disturbances would be an ideal method of approach. Since sperm morphology recorded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 20 publications
4
60
0
5
Order By: Relevance
“…Some studies have reported a correlation between staining of spermatozoa with AB and decreased percentage of normal spermatozoa [28]. Franken et al [16] showed that there was significantly higher percentage of AB positive spermatozoa among men with teratozoospermia when compared with normozoospermic (51% vs. 26%). Despite normal semen analysis in this study, the mean percentage of positive AB staining was 31.6% in the case group and 14.1% in the control group (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported a correlation between staining of spermatozoa with AB and decreased percentage of normal spermatozoa [28]. Franken et al [16] showed that there was significantly higher percentage of AB positive spermatozoa among men with teratozoospermia when compared with normozoospermic (51% vs. 26%). Despite normal semen analysis in this study, the mean percentage of positive AB staining was 31.6% in the case group and 14.1% in the control group (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Three classes of head staining intensities were noted, namely unstained (gray/ white), partially stained, and entire sperm head stained dark blue (Fig. 2) [16].…”
Section: Chromomycin A3 Stainingmentioning
confidence: 99%
“…Aniline blue selectively stains lysine-rich histones (Terquem and Dadoune, 1983) and has been used as a clinical assessment of sperm chromatin condensation and associated infertility (Auger et al, 1990). High percentages of aniline blue-stained spermatozoa were found in patients affected by severe teratozoospermia (Franken et al, 1999), asthenozoospermia (Colleu et al, 1988), varicocele, idiopathic infertility, and with a history of unilateral cryptorchidism (Foresta et al, 1992). Furthermore, higher levels of aniline blue staining were found in subfertile men following cryopreservation than in fertile controls (Hammadeh et al, 1999b).…”
Section: Assessment Of Sperm Chromatin Structure In Fertility Evaluatmentioning
confidence: 99%
“…Two hundred sperm were analyzed on each slide under a light microscope (Leica DM LS, Leica, Wetzlar, Germany). Sperm showing dark-blue staining were considered as AB positive, whereas those stained only weakly or not at all were considered as AB negative (43). After determining the percentage of fragmented sperm in presorted samples, the overall percentage of AB staining in such samples was calculated by (% AB staining in fragmented sperm × % fragmented sperm)/100 + (% AB staining in nonfragmented sperm × % nonfragmented sperm)/100.…”
Section: Staining With Aniline Blue (Ab)mentioning
confidence: 99%